Assessment of weight loss programmes in the Kumasi metropolis - Afriyie –Adjimi, Harriet (KNUST, 2025)
A Thesis Submitted In Partial Fulfilment Of The Award Of The Degree Of Master Of Business Administration (Strategic Management And Consulting-Option).